INTEGRITY FORMS THE BASIS OF A SUCCESSFUL LEADER: USM PRO-CHANCELLOR SHARES HIS THOUGHTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Someone who is born or trained to be a leader need to possess a high standard of integrity.